Impact of White and Dark Red Kidney Beans on Intestinal and Metabolic Health in C57Bl/6 Male Mice - Rodrigue, Alexane (Université d'Ottawa / University of Ottawa, 2019)
Pulses (i.e. beans, lentils, and chickpeas) are enriched in plant-based proteins and non-digestible carbohydrates (e.g. fibre) that may beneficially impact intestinal and metabolic health. The objectives of this thesis were to determine if i) consumption of diet supplemented with kidney beans would improve biomarkers of intestinal and metabolic health, ii) dark-colored beans would provide additional health benefits compared to light-colored beans, and iii) background diet composition would impact the health effects of kidney bean consumption. Study 1: 5-week-old male C57Bl/6 mice were fed either a basal diet (BD; 20% casein, wt/wt), or isocaloric diets supplemented with 15% cooked white kidney beans or dark red kidney beans for 9 weeks (n=12/group); Study 2: 5-week-old male C57Bl/6 mice were fed either a high-fat diet (HF; 60% kcals from fat) or HF diet supplemented with 15% cooked white kidney beans or dark red kidney beans. In both studies, consumption of diets supplemented with beans improved microbiota community structure and activity, as indicated by increased abundance of short-chain fatty acid (SCFA) producing bacteria (Prevotella and S24-7) and intestinal SCFA concentrations, with dark kidney beans inducing the greatest effects. Furthermore, biomarkers of colonic inflammation, barrier integrity, and metabolic health were beneficially impacted by kidney bean consumption, however, the effects were greater in mice consuming low-fat vs. high-fat diets. In conclusion, this thesis demonstrated that while kidney bean consumption led to improvements in intestinal and metabolic health, the results were influenced by seed coat color and the nutrient composition of the background diet.
Keywords: Kidney bean; Pulses; Metabolic Health; Intestinal Health; Microbiota; Short-chain fatty acids